PHILOSOPHICAL BACKGROUND OF RELIGIOUS STUDIES - Victoria Furkalo ("Scientific Information Agency "Science-technologies-information" LLC, 2020)
Achievement of the right ratio of religious studies and religious education is possible under the condition of integration of mental values of individuals and societies, as well as the gradual formation of a single mental space of civilization. It has been established that the philosophical basis of religious studies is that it can: define and form the correct worldview positions regarding religion; offer the person a system of attitudes that excludes negative fluctuations in the search for an appropriate worldview; regulate the axiological positions in the multi-variance of moral choice. In addition, the philosophical basis of religious studies should help to harmonize the content of this education with personal views on the student's religion. This basis should be grounded in the position that religious studies should not impose a certain view of the religions of the world on young people, but should offer a volume of objectively balanced knowledge of religious world view.